2014
DOI: 10.2308/jmar-10406
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of Asymmetric Cost Behavior—Sticky Costs: Expenses versus Cash Flows

Abstract: This note highlights a subtle aspect of the asymmetric costs literature not covered in the comprehensive review by Banker and Byzalov (2014). Specifically, we test the assertion underlying this literature that reported expenses can serve as an appropriate proxy for estimating the asymmetry of economic costs. Our findings refute this assertion, indicating that reporting choices influence the estimated asymmetry level of reported expenses. As a result, reported expenses are significantly more asymmetric (sticky)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 13 publications
7
29
1
1
Order By: Relevance
“…(3) & (4) it turns out the explanatory power are 94.77% for the cost of goods sold and 78.54% for the selling and general and administrative cost which are more better of its peers on the prior literature (e.g. Subramaniam & Weidenmier, 2003;He, et al, 2010;Bosch & Blandón, 2011;Shust & Weiss, 2014;Zanella, et al, 2015;Magheed, 2016;Pamplona, et al, 2016;Jang, et al, 2017) as shown below: In addition, it turns out that the significance of the coefficients of cost stickness in panel A where (β1 = 0.4190, t = 15.64 > 2) ،(β2 = -8.63, t = 10.21 >2) for the cost of goods sold, but it is not significant in panel B where (β1 = -0.0069, t = 0.17 < 2) ، (β2 = -0.0082, t = -0.11 < 2). Besides, it turns out significance of DecDummy*Log (SALESi,t/SALESi,t-1)*Aint ، DecDummy*Log (SALESi,t/SALESi,t-1)*Growth in Panel A where (β3 = -0.2299, t = 5.82 > 2) ،(β4 = -0.1125, t = 5.60 >2), which means that the cost stickness causes represented in asset intensity and economic growth lead to increasing the level of cost stickness for in the cost of goods sold which agree with the prior literature (e.g.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…(3) & (4) it turns out the explanatory power are 94.77% for the cost of goods sold and 78.54% for the selling and general and administrative cost which are more better of its peers on the prior literature (e.g. Subramaniam & Weidenmier, 2003;He, et al, 2010;Bosch & Blandón, 2011;Shust & Weiss, 2014;Zanella, et al, 2015;Magheed, 2016;Pamplona, et al, 2016;Jang, et al, 2017) as shown below: In addition, it turns out that the significance of the coefficients of cost stickness in panel A where (β1 = 0.4190, t = 15.64 > 2) ،(β2 = -8.63, t = 10.21 >2) for the cost of goods sold, but it is not significant in panel B where (β1 = -0.0069, t = 0.17 < 2) ، (β2 = -0.0082, t = -0.11 < 2). Besides, it turns out significance of DecDummy*Log (SALESi,t/SALESi,t-1)*Aint ، DecDummy*Log (SALESi,t/SALESi,t-1)*Growth in Panel A where (β3 = -0.2299, t = 5.82 > 2) ،(β4 = -0.1125, t = 5.60 >2), which means that the cost stickness causes represented in asset intensity and economic growth lead to increasing the level of cost stickness for in the cost of goods sold which agree with the prior literature (e.g.…”
mentioning
confidence: 84%
“…On the other side, the causes of cost stickness differed among the studies when they were explaining the cost stickness phenomenon because of the difference of resource adjustment motives. Consequently, I can determine the most important causes of cost stickness through prior literature in: asset intensity, employee intensity, resource structure, cost structure, operating efficiency in using capacity, strategy, inventory assets, debt intensity, employment laws, and the level of using capacity (See, Subramaniam & Weidenmier, 2003;He, et al, 2010;Bosch & Blandón, 2011;Shust & Weiss, 2014;Apostolos, et al, 2015;Bugeja, et al, 2015;Chae & Chung, 2015;Holzhacker, et al, 2015;Qin, et al, 2015;Zanella, et al, 2015;Magheed, 2016;Pamplona, et al, 2016;Jang, et al, 2017).…”
Section: -Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…() concentrate on earnings as the key input for measuring earnings asymmetric timeliness. If earnings are disaggregated into CFO and accruals, the findings of Shust and Weiss () suggest that it is less likely, but more accurate, to find asymmetry in the cash component than in the accrual component. Shust and Weiss extend Banker et al .…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%